DIET AND FEEDING HABITS OF Chrysichthys nigrodigitatus FROM ORETA AXIS OF LAGOS LAGOON, IKORODU, NIGERIA - BABALOLA, O. A; AZEEZ, Q. A; SUNNUVU, T.F (Nigerian Journal of Fisheries, 2018)
Chrysichthys nigrodigitatus plays a pivotal role in the ecology and fisheries management of brackish water ecosystems. Study on the Diet and Feeding habits of C. nigrodigitatus from Oreta Axis of Lagos Lagoon was carried out between June and August 2017. Parameters such as occurrence and numerical abundance methods, condition factor and stomach condition were evaluated using Windell, 1978, Job and Nyong, 2005 and Asuquo, 2000 procedures respectively. The results on the diet and feeding habits of C. nigrodigitatus showed that the species fed mostly on bivalves and some plant materials. Other food items that were isolated from the gut of the species included; crustaceans parts, small fish, mud/sand particles and detritus. The condition factor computed for the species varied during the study period with a mean value of 0.85 in June, 0.91 in July and 1.05 in August. According to the food items isolated from the gut of the C. nigrodigitatus, the species could be considered as a predatory cum omnivorous category of fish found in Oreta Axis of Lagos lagoon while the progressive increase in the value of the condition factor of the species may indicate a period of high productivity of food preference in the Axis of Oreta.